2018
DOI: 10.1007/s10549-018-4707-0
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall recurrence in pT1-2N0-1 breast cancer patients after mastectomy without radiotherapy

Abstract: The incidence of CWR in pT1-2N0-1 breast cancer patients is very low, especially with isolated recurrence. Also, the obtained data showed that the nodal status had no impact on CWRFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Likewise, a Korean multicenter study (KROG 14–18) also reported that the frequency of local recurrence (6/584 patients) had an incidence of approximately 1/4 for regional recurrence (22/584 patients) [20]. Other recently published results from two Korean multicenter studies (KROG 14–22 and KROG 14–23) showed very low chest wall recurrence rate in patients with <5 cm tumor and 1–3 positive lymph nodes [25]. Based on these results, the authors questioned the necessity of chest wall radiotherapy in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a Korean multicenter study (KROG 14–18) also reported that the frequency of local recurrence (6/584 patients) had an incidence of approximately 1/4 for regional recurrence (22/584 patients) [20]. Other recently published results from two Korean multicenter studies (KROG 14–22 and KROG 14–23) showed very low chest wall recurrence rate in patients with <5 cm tumor and 1–3 positive lymph nodes [25]. Based on these results, the authors questioned the necessity of chest wall radiotherapy in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of loco‐regional failure is likely to reduce with improvement of adjuvant systemic therapies, consequently leading to reduction of PMRT in both relative and absolute benefits 19 . There are studies showing that the risk of 5‐year LRR in patients not receiving PMRT ranged from 3.2% to 6.1% and was still less than 10% even after 10 years of follow‐up 23‐26 . It can be seen that PMRT may be actually of little absolute benefit to pT1‐2N1M0 breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…19 There are studies showing that the risk of 5-year LRR in patients not receiving PMRT ranged from 3.2% to 6.1% and was still less than 10% even after 10 years of follow-up. [23][24][25][26] It can be seen that PMRT may be actually of little absolute benefit to pT1-2N1M0 breast cancer. Recently updated guidelines propose that for pT1-2N1M0 breast cancer patients at low risk of LRR, PMRT may be omitted potentially.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in patients at pathological stage T1‐2 without axillary lymph node metastasis and who did not undergo PMRT, the local recurrence rate was extremely low (1.68%). The study protocol, however, excluded patients with positive margins from the analysis . In a study involving patients at pathological stage T3 without axillary lymph node metastasis who did not undergo PMRT, the locoregional recurrence rate was 7.1%.…”
Section: Discussionmentioning
confidence: 99%